2005
DOI: 10.1128/jvi.79.17.11014-11021.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gene Segments Control the Temperature Sensitivity and Attenuation Phenotypes of ca B/Ann Arbor/1/66

Abstract: Cold-adapted (ca) B/Ann Arbor/1/66 is the influenza B virus strain master donor virus for FluMist, a live, attenuated, influenza virus vaccine licensed in 2003 in the United States. Each FluMist vaccine strain contains six gene segments of the master donor virus; these master donor gene segments control the vaccine's replication and attenuation. These gene segments also express characteristic biological traits in model systems. Unlike most virulent wild-type (wt) influenza B viruses, ca B/Ann Arbor/1/66 is tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 32 publications
0
46
0
9
Order By: Relevance
“…Other genes that do not seem to play a role in temperature sensitivity may still contribute to the att phenotype. Indeed, it has been demonstrated that in addition to the PA and NP genes of B/Ann Arbor/1/66, the M gene also plays a role in attenuation without contributing to the ts phenotype (Hoffmann et al, 2005). Animal studies with selected reassortants will probably reveal the role of each of the genes in attenuation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other genes that do not seem to play a role in temperature sensitivity may still contribute to the att phenotype. Indeed, it has been demonstrated that in addition to the PA and NP genes of B/Ann Arbor/1/66, the M gene also plays a role in attenuation without contributing to the ts phenotype (Hoffmann et al, 2005). Animal studies with selected reassortants will probably reveal the role of each of the genes in attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Of these eight coding mutations, five are in genes coding for the RNP complex (PB2 and PA). Compared to B/USSR/60/69 MDV, the MDV used in FluMist B/Ann Arbor/1/66 contains nine mutations in the genes coding for the internal proteins (one non-unique and eight unique mutations), seven of which are in RNP-encoding genes (PB2, PA and NP) (Hoffmann et al, 2005). In our study we did not find any substitutions at the amino acid level in the PB1 and NP genes in B/USSR/60/69 MDV and we showed that neither of these genes is responsible for manifestation of the ts phenotype of B/USSR/60/60 MDV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of influenza vaccines are currently available, the trivalent or quadrivalent inactivated influenza vaccine (TIV/QIV), which is given intramuscularly, and the live attenuated influenza vaccine (LAIV), which is administered intranasally. LAIV have been engineered by reverse genetics using the HA and NA genes from circulating viruses and an attenuated, temperature-sensitive, cold-adapted backbone, which prevents replication of the virus at temperatures above 33°C, thus limiting virus infection to the upper airways (8,9). Following inhalation of LAIV, the palatine tonsils, the NALT equivalent in humans, is the site where the humoral immune response is initiated (15).…”
Section: Discussionmentioning
confidence: 99%
“…We next assessed the anatomical location of CTL priming following immunization with the LAIV vaccine, which is engineered to preferentially replicate in the lower temperatures of the upper airways (7)(8)(9) and monitored the endogenous CD8 + T-cell response directed against influenza viral proteins. The CD8 + T-cell response following influenza virus infection of C57BL/6 mice is predominately directed against two viral proteins, the nucleoprotein (NP) and acid polymerase (PA) and can be monitored using H-2D b tetramers loaded with the PA 224 and NP 366 epitopes.…”
Section: Significancementioning
confidence: 99%